Analisis Persyaratan Muatan Lokal dalam Peraturan Presiden No. 55/2019 dan Kesesuaiannya dengan GATT dan Perjanjian TRIMs dalam Kerangka WTO - Tisnawan, Nabil Adika; Rosewitha Irawaty (University Of Bengkulu Law Journal, 2023)
This undergraduate thesis discusses the analysis of local content requirements for the electric vehicle industry in Presidential Regulation Number 55 Year 2019 regarding the Acceleration of Battery-Based Electric Vehicles Program for Road Transportation in terms of its compliance with the regulations in the General Agreement on Tariffs and Trade (GATT) and the Agreement on Trade-Related Investment Measures (TRIMs Agreement). The research in this undergraduate thesis is juridical normative. The results of this research conclude that the provisions of local content requirements in Presidential Regulation Number 55 Year 2019 Regarding Acceleration of Battery-Based Electric Vehicles Program for Road Transportation are not in accordance with the regulations of the GATT and the TRIMs Agreement. Article 17 states that companies that meet the requirements of Local Content Value (TKDN) as mentioned in Article 8 can receive fiscal and non-fiscal incentives from the government. This is inconsistent with the provisions of the TRIMs agreement as well as Article III:2 and Article III:4 of the GATT. Therefore, the Indonesian government must make adjustments to the local content requirements for electric vehicles in Presidential Regulation Number 55 Year 2019 so that it is more consistent with its obligations as a member country of the World Trade Organization (WTO).